Do self-compassion and body satisfaction protect women collegiate athletes from disordered eating? - Kit, O.; Petrie, T. A.; Moore, E. W. (Psychology of Sport and Exercise, 2025)
Women athletes are constantly exposed to general societal beauty standards and sport-specific pressures about body weight, food intake, and performance, which lead to negative body perceptions and low body satisfaction and the development of disordered eating (DE) symptoms. Thus, identifying psychosocial resources that can improve athletes' body satisfaction becomes an avenue for reducing their DE symptoms and improving their health. Given the dearth of longitudinal research testing such potential effects, we examined, over a four-month time frame (i.e., Time 1 [T1] vs. Time 2 [T2]), the indirect and direct effects of one such psychosocial resource, self-compassion (SC) on women collegiate athletes' (N = 1678) body satisfaction (BS) and DE symptoms. Through cross-lagged panel analysis, we found that T1 DE (ß = -.10) and T1 SC (ß = .06) contributed inversely and positively, respectively, to athletes' T2 BS. Further, the hypothesized indirect effect of Time 1 SC to Time 2 DE through BS was not significant, ß = -.002, 95 % BCaCI [-.010, .003]; only T1 SC predicted lower levels of DE at T2 (ß = -.08). These findings align with prior cross-sectional research and indicate that women athletes` BS and DE are not likely to spontaneously improve over time, but may be changed through SC-based interventions.